2009
DOI: 10.1099/vir.0.008839-0
|View full text |Cite
|
Sign up to set email alerts
|

Proof of concept for the reduction of classical swine fever infection in pigs by a novel viral polymerase inhibitor

Abstract: 5-[(4-Bromophenyl)methyl]-2-phenyl-5H-imidazo [4,5-c]pyridine (BPIP) is a representative of a class of imidazopyridines with potent in vitro antiviral activity against pestiviruses including classical swine fever virus (CSFV). This study analysed whether the lead compound, BPIP, was able to reduce virus replication in infected piglets. The compound, administered in feed, was readily bioavailable and was well tolerated. Eight specific-pathogen-free pigs received a daily dose of 75 mg kg "1 (mixed in feed) for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…One of the most common anatomopathological findings associated after CSFV infection is found in the tonsil, a target tissue for CSFV replication and wherein the virus persists for more than 30 days post infection (Koenig et al., ; Vrancken et al., ). The most relevant histopathological finding in the tonsil are congestion of the blood vessels along with focal to diffuse areas of haemorrhage (Malswamkima, Rajkhowa, Chandra, & Dutta, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common anatomopathological findings associated after CSFV infection is found in the tonsil, a target tissue for CSFV replication and wherein the virus persists for more than 30 days post infection (Koenig et al., ; Vrancken et al., ). The most relevant histopathological finding in the tonsil are congestion of the blood vessels along with focal to diffuse areas of haemorrhage (Malswamkima, Rajkhowa, Chandra, & Dutta, ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common anatomopathological findings associated after CSFV infection is found in the tonsil, a target tissue for CSFV replication and wherein the virus persists for more than 30 days post infection (Koenig et al, 2007;Vrancken et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…According to the EU strategy to control CSF, affected pigs must be slaughtered and the carcasses buried or destroyed in rendering plants. Nevertheless, anti-virals were tested in pilot trials and have been discussed as a possible primary control measure against virus spread in case of an outbreak, in addition to present countermeasures (Vrancken et al, 2009). Anti-viral substances which prevent or diminish the shedding and spread of CSF virus by infected pigs might offer new additional tools for CSF control (Backer, Vrancken, Neyts, & Goris, 2013;Ribbens, Goris, Neyts, & Dewulf, 2012).…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…Her talk highlighted the potential of antiviral therapy to contain outbreaks of exotic infections, using classical swine fever and the compound BPIP as an example. In experimental studies in piglets, BPIP reduced the viremic period by 74% and the viral load by 1,000-fold, and was highly effective in preventing transmission of infection to untreated sentinels (Vrancken et al, 2009a(Vrancken et al, , 2009b. Modeling studies have shown this to be an economically viable control policy (Backer et al, 2013).…”
Section: Novel Utilization Of Smallpox Medical Countermeasures -Challmentioning
confidence: 99%